2009
DOI: 10.1152/jn.91040.2008
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Responses From the Hindlimb Muscles of the Decerebrate Cat to Horizontal Support Surface Perturbations

Abstract: The sensory and neural mechanisms underlying postural control have received much attention in recent decades but remain poorly understood. Our objectives were 1) to establish the decerebrate cat as an appropriate model for further research into the sensory mechanisms of postural control and 2) to observe what elements of the postural response can be generated by the brain stem and spinal cord. Ten animals were decerebrated using a modified premammillary technique, which consists of a premammillary decerebratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 64 publications
2
67
0
Order By: Relevance
“…The presence of postural responses in decerebrated cats underscores the role of subcortical structures in mediating balance reactions, at least in mammals [21]. It has been suggested that this finding may be generalized to humans in view of a similar reliance of postural reactions on brain stem structures [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of postural responses in decerebrated cats underscores the role of subcortical structures in mediating balance reactions, at least in mammals [21]. It has been suggested that this finding may be generalized to humans in view of a similar reliance of postural reactions on brain stem structures [22].…”
Section: Discussionmentioning
confidence: 98%
“…Perhaps the primarily subcortical nature of postural responses [21,22] requires minimal use of attentional resources. The higher attentional costs observed for walking on visual lines indicated that visuolocomotor demands contributed more to the attentional costs of walking than balance demands.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the results of the present study, these findings show that neuronal mechanisms of the brainstem, cerebellum, and spinal cord are able to maintain lateral stability during locomotion and to compensate for a wide range of destabilizing factors. Decerebrate animals are also able to generate appropriate postural reactions to different perturbations during standing (Musienko et al, 2008;Honeycutt et al, 2009;Honeycutt and Nichols, 2010). One can thus conclude that the feedback control of posture and balance under different conditions is basically the hindbrain and spinal cord function.…”
Section: Discussionmentioning
confidence: 99%
“…It causes strong bilateral activation of back muscles (red lines in Fig. 13D3), which results in an increase of the trunk stiffness (Hu et al, 2009). This increase in stiffness leads to trunk straightening (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation